Chronic pancreatitis is associated with disease-specific regulatory t-cell responses - Schmitz-Winnenthal, Friedrich Hubertus; Kim Pietsch, Dong-Ho; Schimmack, Simon; Bonertz, Andreas; Udonta, Florian; Ge, Yingzi; Galindo Escobedo, Luis Vidal; Specht, Sebastian; Volk, Christine; Zgraggen, Kaspar; Koch, Moritz; Büchler, Markus W.; et al. (Gastroenterology, 2010)
Chronic pancreatitis is characterized by alternating phases of acute inflammation and quiescent disease. Involvement of T-cell responses has been suggested, but pancreatitis-specific T cells have not been described.
Online veröffentlicht am 18. November 2009
Gesehen am 20.06.2023